R, The Effect of Imagery Training on Improving Table Tennis Forehand Drive Skills : The Effect of Imagery Training on Improving Table Tennis Forehand Drive Skills - qayah, ruqayah (UNIB Press, 2025)
Research on table tennis specifically for junior athletes has several important objectives related to the training and development of young athletes. One of the main objectives is to improve basic technical skills, such as forehand drives, backhand drives, serves, and footwork, which are the foundation of table tennis. Furthermore, this study aims to determine the extent to which table tennis training can help develop motor coordination, agility, and reaction speed in junior athletes who are experiencing rapid growth. Another goal is to develop an engaging and enjoyable training model to foster motivation and a strong interest in training in young athletes. The research method used in this study is the experimental method. This method is used based on the consideration that the nature of experimental research is to try something to determine the effect or effect of a treatment. The subjects of the study were 15 junior table tennis athletes of PTMSI Pekanbaru City. The results showed a significant effect of Imagery Training on improving table tennis forehand drive stroke skills. It can be concluded that the implementation of the Imagery Training program resulted in substantial and significant improvements in the subjects' ability to execute accurate and consistent forehand drive strokes.